Native People and the Environmental Regime in the James Bay and Northern Québec Agreement - Peters, Evelyn J. (ARCTIC, 1999)
A major objective of the Cree and Inuit in signing the 1975 James Bay and Northern Quebec Agreement was to protect the environment and thus secure their way of life based on harvesting activities. The main elements of the federal, provincial, and Agreement environmental protection regimes are compared with respect to principles derived from the growing literature on indigenous peoples and environmental assessment. The Agreement contained pioneering provisions for environmental assessment; yet those provisions have not met many of the expectations of the Native people. Part of the dissatisfaction derives from the Agreement itself: some sections are vague and difficult to translate into practices; the advisory committee structures are not well suited to Native cultures; and the right to develop is woven throughout the sections on environmental protection. However, failures and delays in implementing the Agreement have also contributed to this dissatisfaction. These issues have implications for the negotiation strategies of other groups. Un objectif majeur des Cris et des Inuit en signant la Convention de la Baie James et du Nord québécois était de protéger l'environnement et de conserver ainsi leur mode de vie fondé sur les activités d'exploitation des ressources fauniques. On compare les principaux éléments contenus dans les régimes de protection environnementale fédéral, provincial et de la Convention avec les principes tirés de la documentation de plus en plus abondante sur les peuples autochtones et l'évaluation environnementale. La Convention contenait des clauses innovatrices concernant l'évaluation environnementale, mais ces clauses n'ont pas permis de répondre aux attentes des Autochtones. Cette insatisfaction tient en partie à la Convention même: certaines articles sont vagues et difficiles à appliquer concrètement; les structures des comités consultatifs ne conviennent pas bien aux cultures autochtones; et le droit à la mise en valeur se faufile dans tous les articles traitant de la protection ...